(untitled) (Actual Problems of Psychology in Educational Institutions, 2012)
The article presents the results of studying the peculiarities of memory in adolescents. It is established that in the adolescence, logical memory is actively developing. It also rapidly reaches the level that the child moves to the predominant use of this type of memory, and arbitrary and mediated memory. Considered what type of memory prevails in adolescence. The first part contains general information about a teenager, about changes in memory. In the second part, the memory of a teenager was investigated. It is concluded that in the adolescents the level of mechanical memory is gradually decreasing and, accordingly, the speed of logical memory increases.